Kaepernick & America [videorecording (DVD)] - Stephney, Bill, 1962-; Lemon, Don, 1966-; Lemon, Don, 1966-; Battsek, John; Boyer, Nate; Dinwoodie, April; Jackson, Hue (Dark Star Pictures, 2022)
The documentary explores the intersection between Colin Kaepernick's anthem protests and the reactions they spurred in the United States, revealing unique insights into America's ongoing racial turmoil.